2015
DOI: 10.1080/10426507.2014.993035
|View full text |Cite
|
Sign up to set email alerts
|

Recent Achievements in Organic Trithiocarbonates Synthesis

Abstract: Organic trithiocarbonates play a significant role in the synthesis of pharmaceutical, biological, industrial, and natural products. Over the last few years, a number of synthetic procedures for the synthesis of organic trithiocarbonates have emerged. In this review, we summarize the reported activities for the synthesis of organic trithiocarbonates during the last seventeen years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…The fifteen possible CE 3 M 3 + (E=S–Te and M=Li–Cs) combinations satisfy the geometric and electronic criteria to be classified as phC. Remarkably, the phCs here introduced have as a basis well‐known reagents, such as CS 3 2− , CSe 3 2− , and CS 3 Na 2 , [23–25] implying that their experimental realization is feasible.…”
Section: Figurementioning
confidence: 91%
See 1 more Smart Citation
“…The fifteen possible CE 3 M 3 + (E=S–Te and M=Li–Cs) combinations satisfy the geometric and electronic criteria to be classified as phC. Remarkably, the phCs here introduced have as a basis well‐known reagents, such as CS 3 2− , CSe 3 2− , and CS 3 Na 2 , [23–25] implying that their experimental realization is feasible.…”
Section: Figurementioning
confidence: 91%
“…Our computations indicate positive natural charges on C and Li atoms in 3 (q c =+ 0.87 j e j and q Li =+ 0.97 j e j), implying electrostatic repulsion between them. The interacting quantum atoms [19][20][21][22] (IQA) analysis supports a strong repulsion between carbon and lithium (1356. , and CS 3 Na 2 , [23][24][25] implying that their experimental realization is feasible.…”
mentioning
confidence: 99%
“…Thioether, a functional group in organic chemistry that has the structure C-S-C and a highly efficient pharmacophore that is widely concerned in the research of new pesticide creation, is known to be associated with a broad spectrum of pesticidal bioactivities, such as antifungal, antibacterial, insecticidal, acaricidal, nematocidal, antiviral, herbicidal, and plant growth-regulating activity. More recently, the synthesis and bioactivity of thioether derivatives, also in the context of practical applications, has become one of the main areas of interest in medicinal chemistry [9][10][11][12][13]. The purpose of this review was to collate the literature work reported by researchers on thioether derivatives for their various pesticidal activities.…”
Section: Introductionmentioning
confidence: 99%
“…Catalysis plays an increasingly crucial role in chemical processes and is widely used at the heart of the innumerable chemical methodologies from scientific research in academic laboratories to economical research in industrial laboratories . The easy recovery of the catalysts and their reusability can be regarded as the most significant issues facing the modern catalytic processes due to the fact that either the employed catalysts are often very expensive or the targeted products are often very valuable .…”
Section: Introductionmentioning
confidence: 99%
“…Catalysis plays an increasingly crucial role in chemical processes and is widely used at the heart of the innumerable chemical methodologies from scientific research in academic laboratories to economical research in industrial laboratories. [6,[63][64][65][66][67][68][69][70][71][72][73] The easy recovery of the catalysts and their reusability can be regarded as the most significant issues facing the modern catalytic processes due to the fact that either the employed catalysts are often very expensive or the targeted products are often very valuable. [6,[74][75][76][77][78][79][80][81] As compared to the heterogeneous catalysts, homogeneous catalysts exhibit high catalytic activities in chemical processes due to their solubility in the reaction media, which consequently increases catalytic site accessibility for the substrate.…”
Section: Introductionmentioning
confidence: 99%